Analysis of Translation Interjection into English in the Novel Matahari - Annisa Siti Zulfah; Rita Sutjiati Djohan (ITScience (Information Technology and Science), 2023)
Language is a system of sound and character signs used to communicate within and between communities. Interjection is one of the language parts that are commonly used as a daily expression. Translation has a significant role in order to reach the receptor for understanding the source language. The study of this research focuses on the analysis of translation techniques for Interjections in the novel “Matahari” into English. The purpose of this study is to describe the translation techniques applied in translating interjections and to know what translation technique is mostly employed in translating interjections from Indonesian-English in the novel “Matahari”. The researcher conducts a qualitative descriptive method. This study is also conducted by using analyzing the translation technique, comparing and classifying the data, getting the data percentage, and drawing the conclusion. The researcher collectes the data from the novel and there were 45 data. The result of the data analysis shows that there are 13 data (28,9 %) using borrowing, 12 data (26,7%) using literal translation, 5 data (11,1%) using adaptation, 5 data (11,1%) using linguistic amplification, 5 data (11,1%) using established equivalent, 3 data (6,7%) using substitution, and 2 data (4,4%) using amplification. The researcher found the most common technique used is Borrowing.